In Vitro Comparison of Antibacterial and Antibiofilm Activities of Selected Jordanian Honeys with Manuka Honey - Al-Kafaween, Mohammad A.; Al-Hammouri, Hala F.; Harb, Mohammad (Anti-Infective Agents, 2026)
IntroductionHoney is a natural product that has been widely used for its therapeutic effects.ObjectiveThe purpose of this study was to evaluate and compare the antibacterial activity of Jordanian honey (Sidr and Jabali) with Manuka honey against Staphylococcus aureus and Escherichia coli.MethodsThe antibacterial and antibiofilm activities were evaluated using agar well diffusion assay, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), growth curve, time-kill curve, microtiter plate assay and reverse transcription polymerase chain reaction (RT-qPCR).Results and DiscussionAgar well diffusion assay showed that Sidr and Jabali honey had antibacterial activity at 20% (w/v) and 25% (w/v) respectively compared with Manuka at 20% (w/v) against both bacteria. The MIC values for both Manuka and Sidr honey were 20% (w/v) and 25% (w/v) for Jabali honey against both bacteria. The MIC50 values for both Manuka and Sidr honey were 20% (w/v) and 25% (w/v) for Jabali honey against both bacteria. Whereas, the MIC90 values against S. aureus were 25% (w/v) for both Manuka and Sidr honey and 50% (w/v) for Jabali honey. While the MIC90 values against E. coli were 50% (w/v) for both Manuka and Sidr honey and 75% (w/v) for Jabali honey. The MBC values for Manuka and Sidr honey were 25% (w/v) and 50% (w/v) for Jabali honey against both bacteria. The growth curve of S. aureus and E. coli was reduced after exposure to all the tested honeys at MIC. In the time-kill curve assay, S. aureus cells were significantly (P<0.05) decreased to 4.5-log10, 4-log10, and 3.34-log10 after incubation with Manuka, Sidr, and Jabali honey respectively compared to untreated. Meanwhile, after E. coli cells were treated with Manuka, Sidr and Jabali honeys, the number of cells was significantly (P<0.05) decreased to 4.7-log10, 4-log10 and 3.6-log10 reduction respectively compared to untreated. The lowest concentration 20% (w/v) of all the tested honey was able to inhibit and eradicate S. aureus and E. coli biofilms. The RT-qPCR analysis showed that the range of gene expression of argF, purC, pykA, fabG, scdA, adh and menB in S. aureus was between 4.8-6.3-fold, 3.9-5.9-fold and 3.5-5.6-fold after exposure to Manuka, Sidr and Jabali honey respectively. In addition, the range of gene expression of yifO (bsmA), rpoS, ycfR (BhsA), tnaA and evgA in E. coli was between 4.6-6.3-fold, 4.1-5.8-fold and 4-5.4-fold after exposure to Manuka, Sidr and Jabali honey respectively.ConclusionAmong the all-tested honey, Manuka showed the highest total antibacterial activities against both bacteria. This study demonstrated that Sidr and Jabali honey has antibacterial and antibiofilm activities compared with Manuka honey. This study revealed that Sidr and Jabali honey inhibits both of S. aureus and E. coli planktonic and biofilm through the downregulation of genes required for cell envelope stability and motility.
Keywords: E. coli